VO 2 MAX ON WOMEN RECREATION RUNNERS (CASE STUDY ON WOMEN'S RECREATION RUNNERS IN GANTARVELOCITY) - prisca widiawati (Universitas Negeri Malang, 2020)
Physical fitness is a component that is needed by the body. Physical fitness supports a person in carrying out their daily activities. Someone with an unfit body can easily feel tired , which can result in productivity at work . The most appropriate indicator to see physical fitness is to look at the VO 2 max value or the maximum oxygen capacity value . This study is a pre-experimental study that aims to see whether or not there is a difference in the VO 2 max value before the VO 2 value max after the respondent is given training. The data used in this study is secondary data taken from the Gantarvelocity data bank for 2019–2020. The sample used was 30 samples taken by random sampling . The data analysis used is the t-test which will be used to see whether there is a difference in the VO 2 max value before the VO 2 max value after the respondent is given training . B erdasarkan statistical tests that have been done, gained significant value of 0.000 or less than 0.05. This shows that there is a difference between the VO 2 max value before the VO 2 max value after the respondent is given training .